Recommendations from Pediatric and Pediatric Dentistry Associations of the Americas Regarding Pacifier Use - Luana Viviam Moreira; Thainara Caroline Jordão e Silva; Laura Jordana Santos Lima; Maria Eliza da Consolação Soares; Maria Letícia Ramos Jorge; Izabella Barbosa Fernandes (Association of Support to Oral Health Research (APESB), 2024)
Objective: To identify online recommendations from pediatric and pediatric dentistry associations of the Americas regarding the pacifier habit. Material and Methods: A search was conducted on the associations' website (November/2021 to March/2023) to the questions: (1) Recommend using a pacifier?, (2) What care?, (3) Advantages and (4) disadvantages, (5) Ideal age, and (6) methods for habit removal. Results: Among the 36 American countries, 21 were represented on websites, social media, and official guides. The most significant portion of pediatric dentistry associations (23.81%) does not recommend the use of a pacifier if the infant is exclusively breastfeeding, and recommends avoiding the offer of a pacifier in the first days of life to facilitate the establishment of breastfeeding. Some pediatric (29.63%) associations suggested that use reduces the risk of sudden infant death syndrome. Most pediatric dentistry associations (85.71%) and some pediatric associations (22.22%) linked pacifier use to breastfeeding difficulties and the occurrence of orthodontics. Most of the 20 pediatric dentistry associations stated that the habit should be removed by a maximum of three years of age (90.48%). The most reported recommendations were behavior modification techniques and positive reinforcement. Conclusion: Most pediatric dentistry associations recommend the care and disadvantages of pacifiers and the ideal age to remove them. The few pediatric associations that provide information address indications, care, advantages and disadvantages of pacifiers, age, and methods for removing them.